A case study of one-on-one English instruction for a speech-delayed student: Condition, challenges and outcomes - Intan Puspita Sari; Niamika El Khoiri; Yusnita Febrianti (University of Muhammadiyah Malang, 2026)
This study examines how a one-on-one English learning environment supports the attainment of learning outcomes for a speech-delayed learner in an EFL context. The objective of this research is to examine how individualized instruction facilitates participation, engagement, and spoken language development in a learner experiencing expressive speech delay. A qualitative case study design was employed, focusing on a single learner in a private tutoring setting. The data were collected through systematic classroom observations and reflective teaching records during a series of tutoring sessions. The findings indicate that although speech production remained limited and progress was gradual, the one-on-one setting enabled meaningful improvements in learner participation, sustained attention, imitation attempts, and emotional comfort during speaking activities. Flexible instructional pacing, consistent scaffolding, repeated modeling, and multisensory support played significant roles in supporting the learner’s engagement. Reduced communicative pressure within the individualized environment also contributed to decreased anxiety and increased willingness to attempt verbal responses. The study concludes that learning outcomes for speech-delayed learners should be understood as developmental and process-oriented rather than measured solely through linguistic accuracy or fluency. The findings imply that individualized EFL instruction can create supportive conditions that foster attainable and meaningful progress for young learners with speech delays.